Seizures, Focal EEG Abnormalities, and CT - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The prevalence and nature of abnormalities on CT associated with focal EEG abnormalities were evaluated in 964 consecutive children with epileptic and non-epileptic seizures seen over one year at the Royal Liverpool Children's Hospital, England.